STRATEGI PENGEMBANGAN USAHA MIKRO KECIL MILIK WIRAUSAHAWAN WANITA DI NAGARI MATUR HILIA KECAMATAN MATUR - Jasmin Juwandari Putri; Jon Kenedi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Micro and small business managed by women entrepreneurs in Nagari Matur Hilia continue to face various internal and external constraints, including limited capital, weak financial management, low levels of product innovation, and rudimentary marketing practices, despite possessing local economic potential and relatively stable market opportunities. This study's objective is to design development plans to micro also small businesses in Nagari Matur Hilia, Matur District, that are run by female entrepreneurs. The study uses a descriptive methodology that combines quantitative and qualitative techniques with SWOT analysis. The IFAS and EFAS matrices were used to examine information, which were acquired via interviews and observations with sixteen female entrepreneurs from eight jorong and local government representatives. According to the findings, micro and small businesses are situated in the Strength–Opportunity (S–O) strategy quadrant, which reflects both significant external opportunities and comparatively strong internal capabilities. The recommended development strategies include leveraging long-standing business experience to meet relatively stable local market demand, optimizing business locations near residential areas to increase sales to nearby consumers, and enhancing product marketing through social media by utilizing the flexible working hours of women entrepreneurs. These findings underscore the importance of sustained policy support and continuous business mentoring to enhance the competitiveness of women entrepreneurs.